Jesus' Sermon on the Mount : mandating a better righteousness - Lundbom, Jack R. (Minneapolis, Fortress Press, 2015)
"The Sermon on the Mount (Matthew 5-7) is the best-known repository of the teachings of Jesus and one of the most studied. Amid the considerable erudition expended on the Sermon, however, Jack R. Lundbom argues that it has proven too easy to deflect or disregard the main thrust of the Sermon, which he characterizes as a mandate to holy living and a 'greater righteousness.' Through careful attention to the structure of Matthew's Gospel and the place of the Sermon within it, keen sensitivity to the patterns and themes of Israelite prophecy, and judicious comparisons with other Jewish and rabbinic literature, Lundbom elucidates the meaning of the Sermon and its continuity with Israel's prophetic heritage as well as the best of Jewish teaching. By deft appeal to Christian commentators on the Sermon, Lundbom brings its most important themes to life for the contemporary reader, seeking always to understand what the "greater righteousness" to which the Sermon summons might mean for us today"--
Preface -- Abbreviations -- The Sermon on the Mount -- Introduction -- Part I. The sermon on the mount and the gospel of Matthew : 1. Rhetoric and composition in Matthew -- 2. The new covenant in Matthew -- 3. At what elevation is Jesus' sermon on the mount? -- 4. Imitatio Dei in the sermon on the mount -- Part II. The sermon on the mount : 5. Jesus on the mountain (5:1-2) -- 6. The blessings (5:3-12) -- 7. Be salt and light to the world (5:13-16) -- 8. A better righteousness (5:17-20) -- 9. What about anger? (5:21-26) -- 10. Beware of lust (5:27-30) -- 11. What about divorce? (5:31-32) -- 12. Better not to use oaths (5:33-37) -- 13. How to handle insult (5:38-42) -- 14. Love your enemies (5:43-48) -- 15. Beware of public piety (6:1-18) -- 16. Where your treasure is (6:19-21) -- 17. Single-mindedness to God and others (6:22-24) -- 18. Be not anxious about your life (6:25-34) -- 19. Beware of making judgments (7:1-5) -- 20. Give not away what is holy (7:6) -- 21. Ask and it will be given you (7:7-12) -- 22. Enter through the narrow gate (7:13-14) -- 23. Beware of false prophets (7:15-20) -- 24. Hearing and doing is everything (7:21-27) -- 25. And the crowds were astonished (7:28-29) -- Appendix: Jewish, Christian, and classical authors cited.
Includes bibliographical references (pages 287-308) and indexes.
Keywords: Sermon on the mount -- Criticism, interpretation, etc; Sermon on the mount -- Commentaries; Bible. -- Criticism, interpretation, etc; Righteousness -- Biblical teaching